Neurofilament Light Chain and Intermediate HTT Alleles as Combined Biomarkers in Italian ALS Patients - Ingannato, Assunta; Bagnoli, Silvia; Mazzeo, Salvatore; Bessi, Valentina; Matà, Sabrina; Del Mastio, Monica; Lombardi, Gemma; Ferrari, Camilla; Sorbi, Sandro; Nacmias, Benedetta (Frontiers in Neuroscience, 2021)
Objective: To study the possible implication of the two biomarkers, Intermediate Alleles (IAs) of the Huntingtin (HTT) gene and Neurofilament light chain (NfL) levels in plasma, in Amyotrophic lateral sclerosis (ALS) patients. Methods: We analyzed IAs in a cohort of 106 Italian ALS patients and measured plasma NfL levels in 20% of patients of the cohort. We correlated the two biomarkers with clinical phenotypes. Results: IAs were present in 7.5% of patients of our cohort, a frequency higher than that reported in general population. Plasma NfL levels increased with age at onset (p<.05). Patients with bulbar onset had higher plasma NfL concentration (CI -0.61 to -0.06, p = .02) and a later age at onset of the disease (CI -24.78 to -4.93, p = .006) with respect to the spinal onset form. Additionally, two of the patients, with IAs and plasma NfL concentration lower with respect to normal alleles carriers, presented an age at onset higher than the mean of the entire cohort. Conclusions: According to our findings, plasma NfL and IAs of HTT gene may represent potential biomarkers in ALS, providing evidence of a possible implication in clinical phenotype.